2013
DOI: 10.1186/1475-2875-12-328
|View full text |Cite
|
Sign up to set email alerts
|

Malarial parasite diversity in chimpanzees: the value of comparative approaches to ascertain the evolution of Plasmodium falciparum antigens

Abstract: BackgroundPlasmodium falciparum shares its most recent common ancestor with parasites found in African apes; these species constitute the so-called Laverania clade. In this investigation, the evolutionary history of Plasmodium lineages found in chimpanzees (Pan troglodytes) was explored.MethodsHere, the remainders of 74 blood samples collected as part of the chimpanzees’ routine health examinations were studied. For all positive samples with parasite lineages belonging to the Laverania clade, the complete mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 77 publications
4
78
0
Order By: Relevance
“…Several authors have speculated about the possibility that apes could be a source of new Plasmodium infections for humans and vice versa, providing a mosquito species could act as bridge between these different host species (5,17). Several recent studies have indeed reported transfers of Plasmodium from apes to humans or humans to apes in certain conditions, but the mosquitoes involved in these transfers were never identified (4,7,9,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have speculated about the possibility that apes could be a source of new Plasmodium infections for humans and vice versa, providing a mosquito species could act as bridge between these different host species (5,17). Several recent studies have indeed reported transfers of Plasmodium from apes to humans or humans to apes in certain conditions, but the mosquitoes involved in these transfers were never identified (4,7,9,33).…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated that all ape parasites are transmitted by the same three vector species, thus rejecting the hypothesis that vectors could be responsible for the Laverania host specificity. sanctuary (9), suggesting that host switches are possible under certain conditions, and hence that the species barrier might be porous. Therefore, other factors could contribute to this strong host/parasite association observed in natura in the Laveranias.…”
mentioning
confidence: 99%
“…Analysis of var and var-like gene sequences from human and ape Laverania species showed that many characteristics of these genes are conserved across the different Laverania species and that these evolved well before the emergence of all the Laverania species (Larremore et al, 2015). In addition, the var2csa genes, known to be associated with the adherence of P. falciparum-infected erythrocytes to the placenta and placental malaria in humans, have also been identified in P. reichenowi and P. gaboni (Pacheco et al, 2013;Trimnell et al, 2006). However, the question of whether the expression of var genes is also associated with pathogenicity in AGAs remains open.…”
Section: Pathogenicity Of Malaria Parasites In African Great Apesmentioning
confidence: 99%
“…The absence of such ''silent'' variation indicated that these far-flung isolates shared very recent common ancestry. It further demonstrated that subsequent differentiation among regional populations was minimal, and restricted to sites undergoing exceptionally rapid differentiation, i.e., microsatellite repeats, or to sites experiencing strong selective pressure, i.e., drug resistance and immune evasion alleles Ayala, 1998, 2000;Mita et al, 2009aMita et al, , 2009bVinayak et al, 2010;Mita and Tanabe, 2012;Mallick et al, 2013;Pacheco et al, 2013). These findings illustrate the need for a proper context in interpreting patterns of genetic variability or, in this case, what seemed a notable lack of variability.…”
Section: Protozoans Human Impact On the Structure Of Protistan Parasimentioning
confidence: 83%
“…Answering these questions required identifying useful population comparisons (Pacheco et al, 2013). Phylogenetic inferences as to the ultimate origins of P. falciparum required improved sampling.…”
Section: Protozoans Human Impact On the Structure Of Protistan Parasimentioning
confidence: 99%